Pinos transcorticais e gesso associados à aplicação local de plasma rico em plaquetas no tratamento de fratura do III metatarsiano em potro - Watanabe, Marcos Jun [UNESP] (2015)
In horses less than one year of age fractures of the third metacarpal bone (McIII) or metatarsal bone III (MtIII) are mainly attributed to trauma. Open reduction and internal fixation are the most common treatment method. A Quarter Horse filly with three months of age, which weighed 150kg presented a diaphyseal multifragmentar wedge fracture of right MtIII which was treated with transcortical pins and cast, associated with intralesional application of platelet rich plasma (PRP). After two years of surgery, the animal initiated a training program for racing, and six months later, the patient ran its first official match. The choice of therapeutic methods for treating fractures in horses should be one that provides an earlier repair and minor possibility of complications. Thus, the therapy association which was adopted was considered favorable, since allowed full reestablishment of locomotion of the patient and made possible its return to race.